A kind of perovskite fluorescent powder and its rapid synthesis method and use

CN123004409APending Publication Date: 2026-10-30NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611509473.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]为了解决钙钛矿荧光粉在固相反应体系中的离子解离与扩散困难、制备时间长、制备条件苛刻等问题,本发明提出了一种在空气、室温下快速、规模化制备的高性能钙钛矿荧光粉及其方法,并基于该荧光粉的发光特性实现其在照明、显示以及水下可见光通信等多种应用领域的突破

Benefits of technology

[0018](1)本发明采用DDPA作为A位阳离子活化剂,通过DDPA大幅降低了A位阳离子从前驱体中解离的势垒,促进了离子在固相反应体系中的解离与扩散,有效缩短了固相合成中前驱体离子化所需的时间,进而实现了钙钛矿的高效结晶。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123004409A_ABST
    Figure CN123004409A_ABST
Patent Text Reader

Abstract

The application discloses a rapid synthesis method and application of a capsule type perovskite fluorescent powder and belongs to the technical field of fluorescent powder preparation. Additives are used to promote precursor ionization to make perovskite rapidly crystallize, polyethylene is used to wrap nanocrystals to improve stability, and A / X site doping is used to adjust the spectrum in the range of 450-780 nm. The maximum brightness of the fluorescent powder is 915283 cd / m 2 under 365 nm LED excitation, the half-life (LT 50 ) is more than 3.5 years when the luminous efficiency is 1000 cd / m 2 , the LT 50 in water is more than 1600 hours, blue / green light balanced emission is achieved under 450 nm LED excitation, and the optical signal data rates in the 1 / 7 m underwater channel can reach 150 / 86 Mbps. The capsule type perovskite fluorescent powder is prepared through an ion activation strategy, has the advantages of low cost, controllable spectrum and strong stability, and can be applied to the fields of illumination, display, visible light communication and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite phosphor preparation technology, specifically to a method for rapidly preparing high-quality perovskite phosphor in air and room temperature environments, and its applications. Background Technology

[0002] Metal halide perovskites possess excellent spectral tuning capabilities across the entire visible light range, high luminescence purity, and nanosecond-level fluorescence lifetimes, making them ideal light source materials. To avoid the limitations imposed by the perovskite's extreme sensitivity to water, heat, and oxygen, which restricts its commercial application and development, polymers are widely chosen as encapsulation matrices. This combines the excellent luminescent properties of perovskites with the stability and processability advantages of polymers, resulting in high-quality perovskite phosphors. However, during the synthesis process, organic solvents are widely used to drive complete ion dissociation and diffusion, ensuring high-quality crystallization and uniform dispersion of perovskite within the polymer matrix. This incurs high environmental and cost burdens, hindering commercial mass production. Therefore, developing efficient solvent-free solid-phase synthesis techniques to replace liquid-phase synthesis techniques has become an urgent requirement for commercialization.

[0003] Melt extrusion and mechanical grinding, as two main strategies for solid-state synthesis, have attracted widespread attention. Since perovskites typically have low crystallization barriers, sustained high temperatures or high-energy mechanical forces can effectively drive their crystallization. However, the lack of crucial solvation energy in solid-state reactions means that ions are tightly bound within the precursor lattice, resulting in extremely high dissociation and diffusion barriers, leading to prolonged reaction times and more demanding reaction conditions. Excessively high dissociation barriers not only hinder the reaction but also exacerbate phase separation problems in the doped ion system, leading to a series of issues such as decreased material properties and difficulties in spectral control.

[0004] Therefore, developing perovskite phosphor preparation technology suitable for solid-phase reaction systems and solving the problems of ion dissociation and diffusion in a solid-phase environment are crucial for achieving rapid and large-scale preparation of high-quality perovskite phosphors and are key to overcoming the aforementioned application bottlenecks. Summary of the Invention

[0005] To address the challenges of ion dissociation and diffusion, long preparation time, and stringent preparation conditions in solid-phase reaction systems, this invention proposes a method for the rapid and large-scale preparation of high-performance perovskite phosphors in air and at room temperature. Based on the phosphor's luminescent properties, breakthroughs are achieved in various application fields such as lighting, display, and underwater visible light communication.

[0006] In a first aspect, the present invention provides a method for synthesizing capsule-type perovskite phosphors, comprising the following steps:

[0007] The precursor powder, ligand, activator, and polymer matrix of ABX3 are added to a stirring device and mixed evenly in air to obtain the capsule-shaped perovskite phosphor.

[0008] Furthermore, the A-site precursor in the ABX3 precursor powder is either cesium carbonate (Cs2CO3) or formamidine acetate (FAAc), or a mixture thereof.

[0009] Furthermore, the A-site precursor in the ABX3 precursor powder is a mixture of Cs2CO3 and FAAc. The doping ratio of FAAc is 0% to 100%, preferably 30% to 50%, and more preferably 30%, in molar ratio. By replacing CsCO3 with FAAc, the spectrum and fluorescence lifetime of the phosphor can be controlled. As the doping ratio changes, the brightness, spectrum and fluorescence lifetime of the phosphor will also change.

[0010] Furthermore, the B-site precursor in the ABX3 precursor powder is Pb(CH3COO)2·3H2O.

[0011] Furthermore, the X-position precursor in the ABX3 precursor powder is tetrabutylammonium tribromide (TBABr3), tetrabutylammonium chloride (TBACl), or tetrabutylammonium iodide (TBAI).

[0012] Furthermore, the ligand is bis(dodecyl)dimethylammonium bromide (DDAB).

[0013] Furthermore, the activator is a cationic activator, namely dodecylphosphonic acid (DDPA), and the ratio of ABX3 precursor powder, ligand, cationic activator, and polymer matrix is ​​0.2 mmol: 500 mg: 1-2 g: 10 g.

[0014] Furthermore, the mixing and stirring time is 80-120 seconds, preferably 120 seconds, in order to fully coat the polymer, and the rotation speed is above 20,000 rpm.

[0015] Secondly, the present invention provides a capsule-shaped perovskite phosphor prepared by the method described in the first aspect, which has a capsule-shaped structure.

[0016] Thirdly, the present invention provides the use of capsule-shaped perovskite phosphors prepared using the method described in the first aspect in lighting, displays or visible light communications.

[0017] Compared with the prior art, the advantages of the present invention are:

[0018] (1) In this invention, DDPA is used as an A-site cation activator. DDPA significantly reduces the barrier for the dissociation of A-site cations from the precursor, promotes the dissociation and diffusion of ions in the solid-phase reaction system, effectively shortens the time required for precursor ionization in solid-phase synthesis, and thus achieves efficient crystallization of perovskite.

[0019] (2) The reaction system can be completed at room temperature and in air. The reaction process is driven by the mechanical energy of the stirrer, without the need for high temperature or long-term grinding, which reduces the solid-phase reaction conditions and production costs.

[0020] (3) By regulating the doping composition of A-site cations or X-site anions, the spectrum and fluorescence lifetime of the phosphor can be effectively controlled. In addition, the good processing performance of the polymer matrix and its water, heat and light stability endow perovskite phosphors with diverse application forms, and they have excellent application value in the fields of lighting sources, display sources and visible light communication. Attached Figure Description

[0021] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the accompanying drawings used in the description of the specific embodiments or the prior art will be briefly introduced below.

[0022] Figure 1 To compare the role of additive-assisted ion activation strategies in solid-phase reactions in Examples 1, 1, and 2, (a) the changes in ion activation energy during different reaction processes, (b) the XPS spectra of Cs with / without DDPA doping, and (c) the changes in PL luminescence intensity of in-situ synthesized DDPA phosphors with / without doping and photographs of the powders under ultraviolet light.

[0023] Figure 2 The morphological characteristics of the capsule-type PeQD phosphor are shown in (ac) SEM images and statistical data of the size distribution of the phosphor at different reaction times, (df) TEM and elemental mapping images of the phosphor particles, (g) schematic diagram of the PeQD capsule, (h) TEM image of the PeQD encapsulated in the polymer matrix, (i) XRD pattern of the phosphor and lattice stripe images and lattice spacing of the (100) and (110) crystal planes.

[0024] Figure 3 For the photophysical properties of phosphors, (a) different FA + (a) PL spectrum and emission peak wavelength of phosphor at different concentrations; (b) PLQY of phosphor at different peak wavelengths; (c) PLQY of phosphor at different concentrations. + Fluorescence lifetime of phosphor at concentration

[0025] Figure 4For the optical characterization of mixed halide perovskite phosphors, (a) the PL spectrum and UV-lit photograph of Cl / Br mixed halide perovskite phosphor, and (b) the PL spectrum and UV-lit photograph of Br / I mixed halide perovskite phosphor.

[0026] Figure 5 To assess the luminescent properties of green phosphor, (a) the luminescent stability of a light-emitting module excited by a 365nm ultraviolet LED in water (initial luminance 1184 cd / m²). 2 (b) Brightness-voltage curves and PL spectra of phosphor downconversion green LEDs, (c) Measured LT of green LEDs at different brightness levels. 50 The luminescence lifetime and the linear fitting curves of the luminescence lifetime at different brightness levels.

[0027] Figure 6 To illustrate the luminescent performance of phosphor downconversion green LEDs, (ab) PL spectra, emission photographs, and CIE coordinates of green LEDs excited by 365nm LEDs at different voltages, and (cd) PL spectra, emission photographs, and CIE coordinates of blue-green LEDs excited by 450nm LEDs at different voltages, as well as the range of NTSC and Rec.2020 display standards.

[0028] Figure 7 The diagram shows the schematic of an underwater visible light communication system, along with photographs of the experimental setup.

[0029] Figure 8 The data provided are demonstration data for an underwater visible light communication system, showing the BER-data rate curves and corresponding eye diagrams of the communication module in unbalanced / balanced states in underwater channels at depths of 1m and 7m. Detailed Implementation

[0030] The following examples and comparative embodiments further illustrate the content of the present invention, but should not be construed as limiting the present invention. Any modifications and substitutions made to the methods, steps, or conditions of the present invention without departing from the essence of the invention are within the scope of the present invention.

[0031] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0032] The reference to "embodiment" in this application means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.

[0033] The technical term "and / or" in this application is only a description of the relationship between related objects, indicating that there can be three kinds of relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist at the same time, and B exists alone.

[0034] In addition, the character " / " in this application generally indicates that the objects before and after it are in an "or" relationship.

[0035] In the technical solution described in this invention, dodecylphosphonic acid (DDPA) is the A-position cation activator in ABX3. The perovskite precursor is provided by cesium carbonate (Cs2CO3), formamidine acetate (FAAc), lead acetate trihydrate (Pb(CH3COO)2·3H2O), tetrabutylammonium tribromide (TBABr3), tetrabutylammonium chloride (TBACl), and tetrabutylammonium iodide (TBAI), which provide ions at the A, B, and X positions. The ligand is composed of bis(dodecyldimethylammonium bromide) (DDAB), and the polymer matrix is ​​composed of polyethylene (PE) microspheres. The above materials do not require pretreatment; they can be directly weighed and poured into a mixer to begin synthesis. For ease of replication, it is noted that the mixer used in this invention has a power of 0.22 kW and a rotation speed of 22,000 rpm for reference.

[0036] The chemical structure of the precursor material used in the preparation of the phosphor in this application is shown in Formulas 1-9:

[0037]

[0038] Figure 1 This study demonstrates the role of additive-assisted ion activation strategies in solid-phase reactions. Taking DDPA as an example, the coordination interaction between the additive and the Cs precursor reduces the ion binding energy of Cs, thereby lowering the ion activation energy, reducing the reaction barrier, and significantly increasing the dissociation rate. By comparison, the dissociation phase time in the reaction system with DDPA was significantly reduced from over 80 s to 25 s, resulting in a rapid increase in the phosphor luminescence intensity during the crystallization phase.

[0039] To illustrate this invention, the following detailed description, in conjunction with figures, embodiments, and application examples, outlines the raw material formulation, preparation process, corresponding characterization methods, and applications of the RGB perovskite thin film described herein.

[0040] Comparative Example 1: Preparation of pure Cs perovskite phosphor under incomplete reaction:

[0041] Using a common mechanical grinding method, in the synthesis of perovskite phosphor, 10g of PE microsphere powder, 0.1mmol of Cs₂CO₃, 0.2mmol of Pb(CH₃COO)₂·3H₂O, 0.2mmol of TBABr₃, and 500mg of DDAB were added to a metal stirrer. Then, the precursors were mixed and stirred in air at room temperature for 120 seconds to obtain a white, pure Cs perovskite and polymer precursor powder. At this point, the raw materials had not fully reacted, and the luminescence was not obvious.

[0042] Example 1: Preparation of pure Cs perovskite phosphor:

[0043] Using a common mechanical grinding method, in the synthesis of perovskite phosphor, 10 g of PE microsphere powder, 0.1 mmol of Cs₂CO₃, 0.2 mmol of Pb(CH₃COO)₂·3H₂O, 0.2 mmol of TBABr₃, 500 mg of DDAB, and 1 g of DDPA were added to a metal stirrer. Then, the precursors were mixed and stirred in air at room temperature for 120 seconds to obtain a pale yellow pure Cs perovskite phosphor. At this point, the raw materials had fully reacted, and the luminescence was very obvious.

[0044] Example 2: Preparation of Cs / FA-doped perovskite phosphor:

[0045] The other processes are the same as in Example 1, except that Cs2CO3 is partially or completely replaced with FAAc. Specifically, 0.1 mmol Cs2CO3 is replaced with 0.09 mmol Cs2CO3 + 0.02 mmol FAAc, 0.07 mmol Cs2CO3 + 0.06 mmol FAAc, 0.05 mmol Cs2CO3 + 0.1 mmol FAAc, or 0.2 mmol FAAc, respectively. These correspond to molar doping ratios of FAAc of 10%, 30%, 50%, and 100%. As the FA doping ratio increases, the powder color gradually darkens. When all Cs is replaced with FA, the powder turns yellowish-brown, and the emission spectrum under ultraviolet excitation gradually redshifts.

[0046] Figure 2 The morphology and structure of the pure Cs perovskite phosphor prepared in Example 1 are shown. As the reaction proceeds, the particle size of the powder gradually increases, representing the encapsulation and growth of the perovskite nanocrystals by the polymer matrix. Electron microscopy images confirm that the perovskite quantum dots are encapsulated within the polymer matrix, thus the phosphor has a capsule-like structure. This matrix encapsulation and passivation helps improve the environmental stability of the perovskite.

[0047] Figure 3The relationship between the doping ratio (molar ratio) of FA and spectral peak position, PLQY, and fluorescence lifetime is demonstrated. As the FA ratio increases, the spectrum gradually redshifts, and the fluorescence lifetime gradually decreases until all A-sites in the system are replaced by FA. This allows for peak position tuning between 520-540 nm, and fluorescence lifetime tuning between 8-35 ns. Furthermore, when the FA doping ratio is 30%, the PLQY of the phosphor can reach a maximum of 68%.

[0048] The above analysis shows that the sample with a FAAC doping concentration of 30% has the best performance, so this sample will be used for application demonstration in the future.

[0049] Example 3: Preparation of Cl / Br mixed halide perovskite phosphor:

[0050] The other processes are the same as in Example 1, except that TBABr3 is partially replaced with TBACl, that is, 0.2 mmol TBABr3 is changed to 0.1 mmol TBABr3 + 0.3 mmol TBACl, corresponding to a halogen ratio of Cl:Br = 1:1.

[0051] Example 4: Preparation of Br / I mixed halide perovskite phosphor:

[0052] The other processes are the same as in Example 1, except that TBABr3 is partially replaced with TBAI, that is, 0.2 mmol TBABr3 is changed to 0.1 mmol TBABr3 + 0.3 mmol TBAI, corresponding to a halogen ratio Br:I = 1:1.

[0053] Combination Figure 4 Examples 3 and 4 provide preparation schemes for mixed halide perovskite phosphors. Under the excitation of 365nm LED beads, the emission spectra of the perovskite phosphors show cyan and red, respectively.

[0054] Application Example 1:

[0055] Combination Figure 5 This application example demonstrates the illumination potential of perovskite phosphors. The pressed luminescent module achieved a luminescence half-life of up to 1685 hours (1000 cd / m²) in water. 2 (Measured at the brightness level). The light-emitting module, excited by 365nm LED beads, can achieve 915283 cd / m². 2 The maximum brightness, and the working half-life in air derived from the actual brightness-lifetime relationship can reach 3.5 years (1000 cd / m²). 2 The phosphor prepared under the condition of high brightness (measured from the lowest brightness) has excellent luminescent properties and stability, demonstrating its potential for application in stable white light sources.

[0056] Application Example 2:

[0057] Combination Figure 6 This application example demonstrates the lighting potential of perovskite phosphors. Under excitation by 365nm and 450nm LEDs, the emission spectrum of the perovskite phosphor is highly stable. Furthermore, under 450nm excitation, the balance of luminous intensity between the blue and green spectra is excellent, and the CIE coordinates of the blue and green light show consistently stable colors. In addition, the color coordinates of the green light are significantly better than traditional NTSC and even the better Rec.2020 display standard, proving its potential for use as a stable display light source.

[0058] Application Example 3:

[0059] Combination Figure 7 This application example demonstrates the application of the aforementioned green perovskite phosphor in an underwater visible light communication system. The transmitter in the system employs the following components: a 2×10⁶ pseudo-random bit sequence (PRBS) is generated offline and modulated using on-off keying (OOK) in MATLAB. This digital sequence is then converted into an electrical signal using an arbitrary waveform generator (Tektronix AWG710B). The resulting waveform is then processed by a 25dB electrical signal amplifier (Mini-Circuits ZHL-6A-S+) and its amplitude is adjusted using a variable electrical attenuator (VEA). Before driving the 405nm LD (NDV4411T), a broadband DC bias is used to combine the signal with a DC bias voltage. On the receiver side, the incident light first passes through a neutral density filter and a green bandpass filter. The filtered light is then collected by a photomultiplier tube (PMT, model SPCM-02) and converted into an electrical signal. Finally, the output electrical signal was digitized and stored using an oscilloscope (Rohde & Schwarz RTO2024), enabling comprehensive offline analysis such as frame synchronization, symbol detection, and bit error rate (BER) calculation.

[0060] Figure 8 The data rates of optical signals tested in water tank channels of different lengths are presented. In a 1m underwater channel, the data rate within the FEC limit exceeded 150Mbps, and the eye diagrams remained clear at data rates of 140 and 150Mbps, demonstrating low intersymbol interference (ISI). In a 7m underwater channel, the data rate within the FEC limit reached a maximum of 86Mbps, while the eye diagrams remained clear at data rates of 70 and 80Mbps. This demonstrates the application potential of this technology in underwater visible light communication.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be covered within the scope of the claims and specification of the present invention.

Claims

1. A method for synthesizing a capsule-type perovskite phosphor, characterized in that, Includes the following steps: The precursor powder, ligand, activator, and polymer matrix of ABX3 were mixed and stirred evenly in air to obtain the capsule-shaped perovskite phosphor. In the ABX3 precursor powder, the A-site precursor is any one or a combination of Cs2CO3 or FAAc, and the B-site precursor is Pb(CH3COO)2·3H2O.

2. The synthesis method according to claim 1, characterized in that, The A-site precursor in the ABX3 precursor powder is a mixture of Cs2CO3 and FAAc, with the FAAc doping ratio ranging from 0% to 100% in molar ratio.

3. The synthesis method according to claim 1, characterized in that, The X-position precursor in the ABX3 precursor powder is any one or a combination of tetrabutylammonium tribromide, tetrabutylammonium chloride, and tetrabutylammonium iodide.

4. The synthesis method according to claim 1, characterized in that, The ligand is bis(dodecyldimethylammonium bromide).

5. The synthesis method according to claim 1, characterized in that, The activator is a cationic activator, namely dodecylphosphonic acid; and / or, the ratio of ABX3 precursor powder, ligand, cationic activator, and polymer matrix is ​​0.2 mmol: 500 mg: 1-2 g: 10 g.

6. The synthesis method according to claim 1, characterized in that, The mixing time is 80-120 seconds; and / or the speed is 20,000 rpm or more.

7. A capsule-type perovskite phosphor prepared by the method according to any one of claims 1-6, characterized in that, It has a capsule-like structure.

8. Use of a capsule-type perovskite phosphor prepared by the method of any one of claims 1-6 in lighting, display or visible light communication.